EVALUATING THE ASSOCIATION BETWEEN APOLIPOPROTEIN A5 SINGLE NUCLEOTIDE POLYMORPHISMS (APOA5 SNPS) AND HYPERTRIGLYCERIDEMIA - ASLAM , M; FAROOQ, B; MALIK, FA; AJMAL, M; HAMMAD , AR (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was conducted at the Faisalabad Institute of Cardiology from January 2022 to January 2023 to evaluate the association between apolipoprotein A5 single nucleotide polymorphisms (APOA5 SNPS) and hypertriglyceridemia in the Pakistani population and assess the efficacy of fibrate therapy in hypertriglyceridemic patients. Blood samples of patients were collected for DNA extraction by the standard inorganic method. Extracted DNA was analyzed biochemically and genetically following the selection and genotyping of the APOA5 gene to know SNP variants with risk alleles. We analyzed lipid profiles, including TG (triglyceride), HDL (high-density lipoprotein), and LDL (low-density lipoprotein) levels of hypertriglyceridemic patients, then compared them to normal and fibrate-treated individuals. We compared APOA5 (rs662799) SNP (single nucleotide polymorphism) among 50 hypertriglyceridemic, 50 healthy controls, and among the same 50 hypertriglyceridemic patients who were given fibrate. Results showed that fibrate decreased TG level and LDL by about 30-45% and 20-25%, respectively; increased high-density lipoprotein by 10-15% and total cholesterol decreased by 6-8% in Pakistani. Hypertriglyceridemia risk was significantly increased by a minor allele of APOA5 rs662799 polymorphism. Minor allele carriers of rs662799 had an odd ratio of (95% CI) 1.5 (1.03-2.18) (P = 0.032). Risk allele frequency differed among hypertriglyceridemic patients, healthy controls, and fibrate-treated hypertriglyceridemic individuals. We analyzed that 87.5% of healthy controls exhibited no risk allele, while 78% did not show this risk allele among hypertriglyceridemic patients. It was concluded that APOA5 rs662799 polymorphism is a genetic determinant of hypertriglyceridemia. Fibrate caused a reduction in TG and LDL and caused an elevation of HDL-C among hypertriglyceridemic patients.